Enzymatic release of dipeptidyl peptidase‐4 inhibitors (gliptins) from pigeon pea (Cajanus cajan) nutrient reservoir proteins: In silico and in vitro assessments. Issue 12 (1st October 2019) - Boachie, Ruth T.; Okoro, Faith L.; Imai, Kento; Sun, Lu; Elom, Sunday O.; Nwankwo, Joseph O.; Ejike, Chukwunonso E. C. C.; Udenigwe, Chibuike C.
Abstract: In silico and in vitro parameters were used to assess the potential of pigeon pea ( Cajanus cajan ) nutrient reservoir proteins as sources of dipeptidyl peptidase (DPP)‐4 inhibitors. In silico, 40 pigeon pea proteins evaluated had 46% of amino acids associated with DPP‐4 inhibition. After virtual hydrolysis, pepsin had the highest frequency of release and bioactivity of released DPP‐4 inhibiting peptides, compared to papain and thermolysin. In vitro, thermolysin released the most active DPP‐4 inhibitors. The protein hydrolysates contained similar amino acids but different particle sizes. Thus, the bioactivity patterns are attributable to the different nature and behavior of proteins/peptides under actual and virtual conditions. Using eight physicochemical variables, a random forest model with moderate prediction accuracy was developed for predicting DPP‐4 inhibitory activity of papain hydrolysates. The findings demonstrate that proteins from pigeon pea are precursors of DPP‐4 inhibitors, with potential use in formulating functional food for managing type 2 diabetes. Practical applications: The emerging use of in silico simulations to predict bioactivity of peptides can provide a framework to direct further wet lab assessments. This pattern can enhance focusing on factors relevant to the bioactive properties of interest. However, there is still limited evidence to confirm the reliability and accuracy of this tool. This study therefore provides insight into the practical use of in silico simulations to predict bioactivity of food peptides by assessing the factors relevant to the enzymatic release of dipeptidyl peptidase‐4 inhibitors from pigeon pea seed storage proteins and validating the findings with wet lab assessment. This work also provides important information that can enhance the utilization of pigeon pea, which is an orphan crop, in developing functional food products for managing type 2 diabetes mellitus in developing countries. Abstract : In silico and in vitro assessments showed pigeon pea proteins to be sources of DPP‐4 inhibitors. A model was developed to predict the relationship between DPP‐4 inhibitory activity, structural features of the proteins, and biofunctional parameters of released peptides in silico.